The Human Gastric Microbiome Is Predicated upon Infection with Helicobacter pylori - Klymiuk, Ingeborg; Bilgilier, Ceren; Stadlmann, Alexander; Thannesberger, Jakob; Kastner, Marie-Theres; Högenauer, Christoph; Püspök, Andreas; Biowski-Frotz, Susanne; Schrutka-Kölbl, Christiane; Thallinger, Gerhard G.; Steininger, Christoph (Frontiers in Microbiology, 2017)
The human gastric lumen is one of the most hostile environments of the human body suspected to be sterile until the discovery of Helicobacter pylori (H.p.). State of the art next generation sequencing technologies multiply the knowledge on H.p. functional genomics as well as on the colonization of supposed sterile human environments like the gastric habitat. Here we studied in a prospective, multicentre, clinical trial the 16S rRNA gene amplicon based bacterial microbiome in a total of 30 homogenized and frozen gastric biopsy samples from eight geographic locations. The evaluation of the samples for H.p. infection status was done by histopathology and a specific PCR assay. CagA status was determined by a CagA-specific PCR assay. Patients were grouped accordingly as H.p.-negative, H.p.-positive but CagA-negative and H.p.-positive and CagA-positive (n=10, respectively). Here we show that H.p. infection of the gastric habitat dominates the gastric microbiota in most patients and is associated with a significant decrease of the microbial alpha diversity from H.p. negative to H.p. positive with CagA as a considerable factor. The genera Actinomyces, Granulicatella, Veillonella, Fusobacterium, Neisseria, Helicobacter, Streptococcus and Prevotella are significantly different between the H.p.-positive and H.p.-negative sample groups. Differences in microbiota found between CagA-positive and CagA-negative patients were not statistically significant and need to be re-evaluated in larger sample cohorts. In conclusion, H.p. infection dominates the gastric microbiome in a multicentre cohort of patients with varying diagnoses.